Perancangan Sistem Manamejemen Mutu ISO 9001:2015 di Perusahaan Produksi Rempelas - Gregorius Andrew Ang; I Nyoman Sutapa (Jurnal Titra, 2022)
The rempelas production company is a company engaged in sandpaper. The company has two main products, namely cone sandpaper and belt sandpaper. The implementation of ISO 9001:2015 in Rempelas Production Companies is carried out to help companies ensure the quality of the company's quality management system so that the company can expand its market and be able to compete internationally. To be able to meet the ISO 9001:2015 standard, the company needs to fulfill several important documents that can help the company to develop further and explain what is being done and can guarantee the quality management system in the company. The design of ISO begins by analyzing all internal and external issues of the company after a risk analysis is carried out which is then made for completion. With the design of ISO 9001:2015, it can help companies fulfill ISO documents which initially only fulfilled three documents to nineteen documents out of a total of twenty four documents.